Bayaniyah-'i shumarah-'i 5 piramun-i intikahbat-i Majlis-i Shura-yi Islami : (Nihzat-i Azadi-yi Iran)
Statement No. 5- On the elections of the Islamic Consultative Assembly [parliament]: why Nahzati Azadi did not nominate candidates?